Nitrification Rates Are Affected by Biogenic Nitrate and Volatile Organic Compounds in Agricultural Soils - Mohanty, Santosh Ranjan; Nagarjuna, Mounish; Parmar, Rakesh; Ahirwar, Usha; Patra, Ashok; Dubey, Garima; Kollah, Bharati (Frontiers in Microbiology, 2019)
The processes regulating nitrification in soils are not entirely understood. Here we provide evidence that nitrification rates in soil may be affected by complexed nitrate molecules and microbial volatile organic compounds (mVOCs) produced during nitrification. Experiments were carried out to elucidate the overall nature of mVOCs and biogenic nitrates produced by nitrifiers, and their effects on nitrification and redox metabolism. Soils were incubated at three levels of biogenic nitrate. Soils containing biogenic nitrate were compared with soils containing inorganic fertilizer nitrate (KNO3) in terms of redox metabolism potential. Repeated NH4-N addition increased nitrification rates (mMNO3-1 produced g-1 soil d-1) from 0.49 to 0.65. Soils with higher nitrification rates stimulated (p<0.01) abundances of 16S rRNA genes by about 8 times, amoA genes of nitrifying bacteria by about 25 times and amoA genes of nitrifying archaea by about 15 times. Soils with biogenic nitrate and KNO3were incubated under anoxic conditions to undergo anaerobic respiration. The maximum rates of different redox metabolisms (mM electron acceptors reduced g-1 soil d-1) in soil containing biogenic nitrate followed as: NO3 reduction 4.01±0.22, Fe3+ reduction 5.37±0.12, SO42- reduction 9.56±0.16 and CH4 production (µg g-1 soil) 0.46±0.05. Biogenic nitrate inhibited denitrificaton1.4 times more strongly compared to mineral KNO3. Raman spectra indicated that aliphatic hydrocarbons increased in soil during nitrification, and these compounds probably bind to NO3 to form biogenic nitrate. The mVOCs produced by nitrifiers enhanced (p<0.05) nitrification rates and abundances of nitrifying bacteria. Experiments suggest that biogenic nitrate and mVOCs affect nitrification and redox metabolism in soil.